Taking a risk to develop reflective skills in business practitioners. Issue 3 (2nd April 2016) - Mackay, Margaret; Tymon, Alex
Abstract : Critical reflection can support alternative decision-making in business practice. This paper examines the effectiveness of a risk-based pedagogy to engage practitioners in reflective thinking. Educators adopting a radical pedagogy in professionally accredited programmes face multiple challenges: learners often resist the process of self-reflection and stakeholders expect instrumental outcomes. A longitudinal study of human resource practitioners uses an interpretivist methodology to examine reflection through student-led learning and experiential activity. Findings show that a pedagogical method that overturns learner expectations stimulates dynamic discussion and reflection on experience. Implications are that effective risk-based teaching relies on establishing two conditions: (1) a scaffold structure which supports learner improvisation and (2) a lecturer willingness to continually orchestrate chance elements to maximise learning. This study contributes a practice-based understanding of the theoretical development of risk pedagogy, and adds new insights on the process of facilitating reflective skills to enable business practitioners to confront unpredictable work situations.